(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The analysis of forage quality of cocksfoot (Dactylis glomerata L.) and tall fescue (Festuca arundinacea Schreb.) (pure swards) and their mixtures with three subterranean clover (Trifolium subterraneum L.) subspecies in the followed relations: grass + Trifolium subterraneum ssp. brachycalicinum (50:50%); grass + Trifolium subterraneum ssp. yaninicum (50:50%); grass + Trifolium subterraneum ssp. subterraneum (50:50%); grass + Trifolium subterraneum ssp. brachycalicinum +Trifolium subterraneum ssp. yaninicum + Trifolium subterraneum ssp. subterraneum (25:25:25:25%) was performed. The field experiment was carried out at the Institute of Forage Crops, Pleven, Bulgaria (2011-2013). It was found that Trifolium subterraneum ssp. brachycalicinum in mixture with cocksfoot improves principal chemical composition and in vitro digestibility of forage biomass dry matter. The energy feeding value (Feed units for milk and Feed units for growth) was the highest for the mixtures of cocksfoot with Trifolium subterraneum ssp. brachycalicinum. The protein feeding value (Total digestible protein, PDIN, PDIE) significantly increased for all kind of cocksfoot – subterranean clover mixtures. Their forage quality was improved in comparison with the same mixtures of tall fescue. The principal chemical composition of forage obtained from cocksfoot – subterranean clover mixtures was more balanced - in vitro digestibility, net energy and protein feeding value were found be higher